Spina Bifida and Carbamazepine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The records of all pregnant Medicaid recipients in Michigan who were taking anti-epileptic agents during pregnancy were studied at the Center for Drug Evaluation and Research, Food and Drug Administration, Rockville, Maryland.